Inclusion compounds of indomethacin with hydroxypropyl-beta-cyclodextrin: dissolution profile and partition coefficient evaluation (Revista Brasileira de Ciências Farmacêuticas, 2006)
Indomethacin, a non steroidal anti-inflamatory, is practically water insoluble. Hydroxypropyl-beta-cyclodextrin grants better solubility characteristics to included drugs. Indomethacin's complexation protects from hydrolysis, enhancing solubility and dissolution. The aim is to study the influence of complexation methods, freeze and spray-dryer, on indomethacin dissolution and partition coefficient. Dissolution results show that freeze-dried inclusion complex has a better time needed to dissolve 50% and 90% - 1 and 1.8 minutes then other products. The same happens with percentage of indomethacin dissolved at 5, 30 and 60 minutes - 92.6±1.8%; 98.9±1.2% e 100.01±0.1% and also with dissolution efficiency and dissolution profile. Partition coefficient results with the complexes obtained by both methods corroborate the theory that there are several intervenient strengths on this process and not only drug's free fraction that regulates transport to organic phase, reinforcing the environmental pH significance. With phosphate buffer pH 7.0, variations on transport grade by cyclodextrin addition are very small, showing no significant changes on log P*. With phosphate buffer pH 5.5, although not significant, variations are slightly higher. We can conclude that complexation enhances dissolution capacities of lipophylic drugs without changing the characteristics that give them a good ability for membrane diffusion.